Literature and Society: Singir's Structure and Function for the Javanese Santri Community - M. Adib Misbachul Islam; Minatur Rokhim; Muhammad Nida' Fadlan (Buletin Al-Turas, 2020)
AbstractThis article aimed to examine the structure of Javanese singir as an adaptation work of poetry tradition originating from outside Javanese culture and its function for the reading community. This study compared the six Javanese singirs of the library of Universitas Indonesia (Singir Ahli Suwarga, Singir Dagang, Singir Kiamat, Singir Nasihat Jaman Akhir, Singir Patimah, and Singir Santri) with some Arabic and Malay poetry and then discussed them in the social context of Javanese coastal communities. Through a comparative structural approach and sociological studies, this article found that Javanese singir was structurally linked with Arabic poetry rather than with Malay poetry. This could be found in the metrum system which was close to the metrum of kamil majzu’, and various rhyming patterns which were a combination of murabba’ rhyme and muzdawij. The influence of Malay poetry in the six singirs seemed to have little effect, which was limited to aspects of the rhyme pattern a-a-a-a, b-b-b-b that were not fully used. Through an examination of the connection between the six singirs and the reading community, this article also  found that there were two functions of singir; entertaining, and didactic functions that taught various social and religious aspects to the Javanese santri community.